2020
DOI: 10.1088/1757-899x/881/1/012095
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ZnO Nano-fluids on Heat Treatments of Medium Carbon Steel

Abstract: Conventional quenching versus ZnO-NP emulsion and heat treatments for medium carbon steel (CK45) has been carried out in laboratory environment condition. For comparison, the mechanical properties of CK45 and microstructure were examined. The main parameter focused in this work was the concentration of ZnO-NP in deionized water. Thus, emulsion represents a quenching medium for CK45 specimens. Optical microscope analysis for CK45 microstructure, hardness and tensile test for all specimens were done to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Nanofluids, with their cooling and lubricating properties, have emerged as a promising solution [79] E. Nanofluids used as heat treatment of materials Nanofluids have been considered for vast areas of applications as assortment and the multifaceted nature of the nanofluid frameworks, no understanding has been consummated on the particle-size of most potential advantages of utilizing nanofluids for heat transfer applications [80]. Safaa M et al [80] concentrated their research on new additive for water quenching media for medium carbon steel (CK45). The ZnO nanoparticles shows significant effects on cooling rate by promoting the cooling rate at 1 wt.…”
Section: Nanofluids As Coolant In Machiningmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanofluids, with their cooling and lubricating properties, have emerged as a promising solution [79] E. Nanofluids used as heat treatment of materials Nanofluids have been considered for vast areas of applications as assortment and the multifaceted nature of the nanofluid frameworks, no understanding has been consummated on the particle-size of most potential advantages of utilizing nanofluids for heat transfer applications [80]. Safaa M et al [80] concentrated their research on new additive for water quenching media for medium carbon steel (CK45). The ZnO nanoparticles shows significant effects on cooling rate by promoting the cooling rate at 1 wt.…”
Section: Nanofluids As Coolant In Machiningmentioning
confidence: 99%
“…The refrigeration industry is progressively making efforts to replace traditional refrigerants with ones that have less impact on the environment. However, studies on potential replacements such as R1234ze or R1234yf or R450A have indicated that they yield lower heat transfer performance than the refrigerants they are intended to replace [80,[83][84].…”
Section: F Nano-refrigerantsmentioning
confidence: 99%